Dalihan Na Tolu as the Actualization of the Value of Mawaddah wa Rahmah in QS. Ar-Rum [30]: 21: Living Qur'an Study in Sidapdap Simanosor Village, South Tapanuli Regency - Azimah, Miftah Fauzan; Arifin, Zainal (Universitas Islam Negeri Raden Intan Lampung, 2026)
Divorce and domestic conflict are often related to the weak implementation of family responsibilities, communication, and social support. QS. Ar-Rum [30]: 21 places mawaddah wa rahmah as the basis for forming a peaceful family, but studies on its actualization still tend to focus on husband-wife relations and have not examined much the role of local kinship institutions. This study analyzes the understanding, transmission, and actualization of the value of mawaddah wa rahmah through Dalihan Na Tolu in Sidapdap Simanosor Village. This field research uses a qualitative design with a Living Qur'an approach. Data were obtained through observation, in-depth interviews with informants, and documentation, then analyzed descriptively-interpretively through data reduction, presentation, and verification. The results of the study indicate that mawaddah is actualized through responsibility, solidarity, labor and material assistance, and the practice of marsialapari, while rahmah is realized through protection, persuasive communication, speech systems, family gatherings, and mediation of relatives. From the perspective of the Living Qur'an, these values ​​operate at informative, transformative, and performative levels. This finding confirms that Dalihan Na Tolu is a social medium for the actualization of the values ​​of QS. Ar-Rum [30]: 21 by expanding the love and mercy from the ethics of couples to the ethics of the extended family, without neglecting justice, safety, equality, and protection of vulnerable family members.